PENGARUH KUALITAS PELAYANAN, AKSES, DAN KOMPETENSI FISKUS TERHADAP KEPUASAN PEMENUHAN KEWAJIBAN PERPAJAKAN WAJIB PAJAK BADAN - Fitrio Ramadhani; Vince Ratnawati; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of service quality, acces, and fiskus competence to the tax satisfaction fulfillment of corporate taxpayers. The population in this study is the taxpayers and listed on KPP Madya Pekanbaru.The sampling technique using purposive sampling method and determination of sampel size in this study was calculated by formula slovin obtained by 100 respondents. The data of this research using primary data directly through a questionnaires and analyzed using SPSS 20.0. The data were analyzed to test the hypothesis using multiple linear regression analsys approach.The result of this study showed that service quality, acces, and fiskus competence have effect on tax satisfaction fulfillment of corporate taxpayers.Keywords: service quality, acces, fiskus competence, and tax satisfaction